Study of structural network connectivity using DTI tractography in insomnia disorder - Rostampour, Masoumeh; Gharaylou, Zeinab; Rostampour, Ali; Shahbodaghy, Fatemeh; Zarei, Mojtaba; Fadaei, Reza; Khazaie, Habibolah (Psychiatry research. Neuroimaging, 2023)
•Structural connectivity is reduced in patients with insomnia compared to controls.•The existence of false positive connections in reconstructions can significantly affect the accuracy of tractography.•Tractogram filtering may be helpful to reduce implausible connections and identify subnetworks with the most likely structural connectivity between them. Most of tractography studies on insomnia disorder (ID) have reported decreased structural connectivity between cortical and subcortical structures. Tractography based on standard diffusion tensor imaging (DTI) can generate high number of false-positive streamlines connections between gray matter regions. In the present study, we employed the convex optimization modeling for microstructure informed tractography-2 (COMMIT2) to improve the accuracy of the reconstructed whole-brain connectome and filter implausible brain connections in 28 patients with ID and compared with 27 healthy controls. Then, we used NBS-predict (a prediction-based extension to the network-based statistic method) in the COMMIT2-weighted connectome. Our results revealed decreased structural connectivity between subregions of the left somatomotor, ventral attention, frontoparietal, dorsal attention and default mode networks in the insomnia group. Moreover, there is a negative correlation between sleep efficiency and structural connectivity within the left frontoparietal, visual, default mode network, limbic, dorsal attention, right dorsal attention as well as right default mode networks. By comparing with standard connectivity analysis, we showed that by removing of false-positive streamlines connections after COMMIT2 filtering, abnormal structural connectivity was reduced in patients with ID compared to controls. Our results demonstrate the importance of improving the accuracy of tractography for understanding structural connectivity networks in ID.